2007 IEEE Conference on Computer Vision and Pattern Recognition 2007
DOI: 10.1109/cvpr.2007.383252
|View full text |Cite
|
Sign up to set email alerts
|

Handwritten Carbon Form Preprocessing Based on Markov Random Field

Abstract: This paper proposes a statistical approach to degraded handwritten form image preprocessing including binarization and form line removal. The degraded image is modeled by a Markov Random Field (MRF) where the prior is learnt from a training set of high quality binarized images, and the probabilistic density is learnt on-the-fly from the gray-level histogram of input image. We also modified the MRF model to implement form line removal. Test results of our approach show excellent performance on the data set of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 17 publications
(33 reference statements)
0
16
0
Order By: Relevance
“…For example, in Cao and Govindaraju's work [13], the patchbased MRF shape modeling was trained on pre-defined shape patterns to recover the deformations of image shapes. The authors reported significant improvements over traditional approaches using a database of handwritten carbon forms.…”
Section: Related Workmentioning
confidence: 99%
“…For example, in Cao and Govindaraju's work [13], the patchbased MRF shape modeling was trained on pre-defined shape patterns to recover the deformations of image shapes. The authors reported significant improvements over traditional approaches using a database of handwritten carbon forms.…”
Section: Related Workmentioning
confidence: 99%
“…We use the MRF based document image preprocessing algorithm [3] to binarize the form image and remove the grid lines from the image. Assuming the binarized objective image is x and the grayscale image is y, we solve the maximum a posteriori (MAP) estimation x = argmax x Pr(x|y) using the Markov Random Fields (MRF).…”
Section: The Positions Of Two Anchoring Regions In Any Testmentioning
confidence: 99%
“…Many techniques work well on clean images of good quality, but their performance deteriorates when lines are badly broken due to light printing or scanning, low input resolutions, or significant overlap with handwriting on the page [5].…”
Section: Introductionmentioning
confidence: 99%